1989
DOI: 10.1677/joe.0.1200135
|View full text |Cite
|
Sign up to set email alerts
|

Stress alters immune function and disease resistance in chinook salmon (Oncorhynchus tshawytscha)

Abstract: We examined the effects of acute stress on the immune system and disease resistance of juvenile chinook salmon (Oncorhynchus tshawytscha) in laboratory and clinical trials. Immune function, as measured by the ability of lymphocytes from the anterior kidney to generate specific antibody-producing cells (APC) in vitro, was depressed 4 h after stress, when plasma cortisol levels were highest. At the same time, resistance to the fish pathogen, Vibrio anguillarum, was also depressed. Compared with controls, plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
165
2
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(174 citation statements)
references
References 0 publications
4
165
2
3
Order By: Relevance
“…In contrast, in Atlantic salmon IP vaccination [69] was found to elicit a stress response, consisting in the reduction of antibody producing cells and lymphopenia, whose duration exceeded that elicited by other acute stressors such as holding in a dip-net for 30 s [70] or crowding [6].…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, in Atlantic salmon IP vaccination [69] was found to elicit a stress response, consisting in the reduction of antibody producing cells and lymphopenia, whose duration exceeded that elicited by other acute stressors such as holding in a dip-net for 30 s [70] or crowding [6].…”
Section: Discussionmentioning
confidence: 75%
“…Studies in laboratory animals (Dhabhar andMcEwen 1997), livestock (Salak-Johnson andMcGlone 2007), fish (Maule et al 1989) and humans (Biondi and Zannino 1997) have indicated that stress can affect patterns of infectious disease (Sheridan et al 1994). Stress has also been suggested as a factor influencing a wide range of diseases in wildlife, including Chlamydia infection in koalas (Brearley et al 2013), toxoplasmosis in various marsupials (Thompson et al 2010), chytridimycosis in amphibians (Blaustein et al 2012;Kindermann et al 2012;Gabor et al 2013), avian influenza in migratory birds (Weber and Stilianakis 2007) and white nose syndrome (Cryan et al 2010) and zoonotic (spread from animals to humans) viruses in bats, including Ebola and Hendra virus (HeV) (Groseth et al 2007;Plowright et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol release is the most important response stress in the fish (Mazeaud and Mazeaud, 1981;Camacho, 1999;Belo, 2002;Brum, 2003). Its elevated concentration reduces the defense response of the fish (Pickering and Pottinger, 1985;Maule et al, 1989;Belo, 2002;Brum, 2003) and results in increased susceptibility to parasitic and infeccious diseases (Barton and Iwama, 1991). Vitamins and minerals are important in the physiological processes minimizing the effects of stressor agents.…”
Section: Introductionmentioning
confidence: 99%